Validation of an in-house HPV CerviSens self-sampling kit: comparison against clinician-collected and self-collected samples - Arora, Preeti; Jawale, Shruti; Gupte, Sanjay; Shah, Sarjan (Frontiers in Medical Technology, 2025)
IntroductionCervical cancer (CA cervix) ranks as the second most common cancer among women aged 15–44 and remains a leading cause of cancer-related mortality. Regular screening for cervical cancer significantly reduces mortality rates. Due to the strong causal relationship between high-risk human papillomavirus (hrHPV) and cervical cancer, HPV DNA testing has been developed as a screening method. HPV self-sampling kits have the potential to increase screening uptake, facilitate early detection, and reduce the global burden of cervical cancer. This study evaluates the efficacy of an in-house developed HPV CerviSens self-sampling kit for women in detecting hrHPV types.MethodologyThe study, approved by the Gupte Hospital Ethics Committee, included women aged 35–65 visiting Gupte Hospital in Pune, India. Participants self-collected vaginal samples using the in-house developed HPV CerviSens kit, and trained healthcare practitioners collected conventional samples. HPV DNA analysis was performed using the Cobas 4800 assay. Concordance between self-sampling and clinician sampling was assessed using Cohen's κ statistic. The sensitivity and specificity of HPV detection in self-samples were calculated with clinician-collected samples as the reference standard.ResultsA total of 203 paired self-collected and clinician-collected samples were analyzed for HPV detection. The median age of participants was 44 years. Concordance for HPV detection between self-samples and clinician-collected samples was very good (Cohen's κ: 0.88, 95% CI: κ ≥ 0.81). For HPV detection in self-samples, the in-house HPV CerviSens self-sampling kit demonstrated a sensitivity of 98.0% (95% CI: 89.4%–99.9%) and a specificity of 99.4% (95% CI: 96.3%–99.9%) when clinician-collected samples were used as the reference standard. These results demonstrate that the self-sampling method provides high accuracy in identifying high-risk HPV infections.ConclusionHPV self-sampling using the in-house developed HPV CerviSens kit is a reliable and effective method for cervical cancer screening, with high concordance and accuracy in detecting HPV infections. Integrating self-sampling into screening programs can enhance early detection, improve patient outcomes, and significantly reduce the global burden of cervical cancer.